Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Opening Ceremony of the Third International Conference on Chemical Engineering and Industrial Biotechnology 2016 - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
It is indeed a great honour for us in UMP to be entrusted with the responsibility of hosting the third edition of this bi-annual conference and to receive speakers, delegates and participants of different nationalities from all over the world who I believe, are really enthusiastic to share their intellectual thoughts and research findings relating to current issues in the areas of Chemical Engineering and Industrial Biotechnology.